The medial habenula: still neglected - Viswanath, Humsini; Carter, Asasia Q.; Baldwin, Philip R.; Molfese, David L.; Salas, Ramiro (Frontiers in Human Neuroscience, 2014)
The habenula is a small, bilateral brain structure located at the dorsal end of the diencephalon. This structure sends projections to the dopaminergic striatum and receives inputs from the limbic forebrain, making the habenula a unique modulator of cross-talk between these brain regions. Despite strong interest in the habenula during the seventies and eighties (1-5), interest waned due to lack of a clearly identifiable functional role. Following Matsumoto and Hikosaka’s seminal work on the lateral habenula as a predictor of negative reward in monkeys, the habenula has undergone a resurgence of scientific interest. Matsumoto and Hikosaka demonstrated an increase in habenular neuron firing when monkeys did not receive an expected juice reward (6). Studies have shown that increased habenular activity inactivates dopaminergic cells in the Rostromedial Tegmental Nucleus (RMTg) through GABAergic mechanisms (7, 8). Additional studies link habenular activity to the regulation of serotonin and norepinephrine, suggesting the habenula modulates multiple brain systems (9, 10). These discoveries ushered in a series of new studies that have refocused attention on the lateral habenula and the importance of this small brain structure (7, 11-14). Recently, Geisler and Trimble reviewed this renewed interest in: The Lateral Habenula: No Longer Neglected (15). While the lateral habenula (LHb) has been extensively studied, the anatomically and histochemically distinct medial habenula (MHb) remains largely understudied. This short review argues that the MHb is functionally important and should be studied more aggressively.